2022
DOI: 10.1002/jgh3.12718
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lymph node metastasis and indication of local resection in duodenal neuroendocrine tumors

Abstract: Background and Aim: The risk factors for lymph node metastasis (LNM) of duodenal neuroendocrine tumors (DNETs) are not well identified, and a definitive standard of treatment for DNETs has not been established. In this study, we aimed to identify the risk factors for LNM and establish the indication of local resection for DNETs. Methods: We retrospectively reviewed 55 patients with 60 non-ampullary and nonfunctional DNETs. We evaluated the risk factors for LNM and compared the outcomes between endoscopic resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…There are no epidemiological research data on DNETs in China. In recent years, with the continuous improvement of diagnostic technology, the incidence rate of DNETs has increased[ 9 ], but there is still insufficient clinical knowledge and management of DNETs[ 10 ]. This study retrospectively analysed the clinical characteristics and prognosis of single centre confirmed DNET patients to help guide disease management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no epidemiological research data on DNETs in China. In recent years, with the continuous improvement of diagnostic technology, the incidence rate of DNETs has increased[ 9 ], but there is still insufficient clinical knowledge and management of DNETs[ 10 ]. This study retrospectively analysed the clinical characteristics and prognosis of single centre confirmed DNET patients to help guide disease management.…”
Section: Discussionmentioning
confidence: 99%
“…In functional DNETs, ZES accounts for a higher proportion, and somatostatin tumours are rare[ 1 , 10 ]. There is only one case of functional DNETs in this centre, which is a ZES patient in the ampullary region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, few studies have constructed models to predict LNM and survival in patients with duodenal malignant tumours via radiomics analysis [ 23 ]. Previous studies have shown that T stage and lymph vessel invasion are independent risk factors for LNM [ 24 26 ]. Our results are consistent with the above studies, and it is reasonable that surgery should be performed for DPC in advanced stages.…”
Section: Discussionmentioning
confidence: 99%
“…Although no consensus has been reached, it has been reported that the risk factors for the metastasis of NAD-NETs are tumors >10 mm in diameter, muscular invasion, poorly differentiated neuroendocrine histology, and lymphovascular invasion ( 20 , 21 ). Nakao et al found that a tumor size ≥10 mm, positive lymphovascular invasion, and 0–Is morphology were significant risk factors for lymph node metastasis ( 22 ). A recent study assessing risk factors for metastases in nonampullary lesions <20 mm in size revealed lymphovascular invasion, tumor size >11 mm and WHO G2 as risk factors for metastatic disease ( 23 ).…”
Section: Discussionmentioning
confidence: 99%